Cardiopulmonary fitness test among Nepalese students - Hada, S; Amatya, S; Gautam, K (Janaki Medical College Journal of Medical Science, 2013)
Background and Objectives: Maximum Oxygen uptake (VO2 max) is a good predictor of cardiopulmonary and muscle fitness. Maximum oxygen uptake is defined as the highest rate at which oxygen can be taken up and utilize by body during severe exercise. The present study aims to find out the level of VO2 max using Mc Ardle equation and to compare obtained values from Chatterjee’s equation in Nepalese population. Methodology: Maximum oxygen uptake was determined by using the Queen’s college step-stool of 16.25 inches and popular Mc Ardle equation. Stepping was done for a total duration of 3 minutes at the rate of 24 cycles per minute for males and 22 cycles per minute for females. After completion of the exercise, subjects remained standing while the carotid pulse rate was taken as heart rate. Maximum oxygen uptake was calculated using obtained heart rate. Results: Queen’s college step test (QCT) was used as a submaximal exercise and the estimated VO2 max in boys and girls was 48.8± 7.3 ml/kg/min and 37.4± 2.7 ml/kg/min respectively with Mc Ardle equation and the value was higher when compared with Chatterjee’s equations. The value of VO2 max was observed and found to be less in smokers and sedentary individuals. Conclusion: As the values of VO2 max obtained from different equations are different, this research strongly argues the need of developing a prediction equation specifically for the Nepalese population. DOI: http://dx.doi.org/10.3126/jmcjms.v1i1.7879 Janaki Medical College Journal of Medical Sciences (2013) Vol. 1 (1):3-8